Enhancing Sustainability in Linear WSNs Using DSDVTRI: A Triple-Interleaving Routing Approach for Pipeline Monitoring - Kumaran, Divya Nacciar; Siva Kumar Subramaniam; Ahamed Fayeez Bin Tuani Ibrahim; Vigneswara Rao Gannapathy (Advance Sustainable Science Engineering and Technology, 2026)
The safety and efficiency of oil and gas pipelines remain critical due to the high risks associated with leaks, pressure surges, and undetected structural damage. WSNs provide an effective solution for real-time monitoring by deploying sensor nodes along the pipeline. However, existing routing protocols such as DSDV and AODV face challenges with congestion, packet loss, and uneven energy consumption in long linear topologies. This study proposes DSDVTRI, a triple-interleaving extension of the DSDV protocol designed to improve data delivery and energy efficiency in linear pipeline networks. Simulations were performed using NS2.35 version across node counts ranging from 20 to 200. The results show that at number of nodes 100, DSDVTRI improves throughput by 14.2% and delivery ratio by 3.05% compared to DSDV, while reducing energy consumption per packet by 6.3%. These findings demonstrate that DSDVTRI enhances performance stability, making it suitable for real-time and energy-efficient pipeline monitoring applications.